Does counters’ responsibility end at the margin of the marginal utility? Reflection on „The Marginal Utilities and Marginal Costs of Having Children” by Péter Mihályi - Pulay, Gyula (Public Finance Quarterly, 2020)
In his article published in the 2019/4 issue of the Public Finance Quarterly, Péter Mihályi argues that in Hungary, population reduction and aging cannot be significantly reduced within national frameworks, no matter how large the amount of money by which the state tries to reduce the individual costs of childbearing is. In contrast, on the one hand, this article points out that there are realistic options for reducing the gap between the number of children desired and the number of children actually delivered, and thereby significantly increasing the fertility rate. On the other hand, the article outlines a number of factors (emigration, high rates of childlessness) that should be taken into account when designing a model for the individual utility of childbearing, and thus give families additional aspects to consider when making decisions in terms of childbearing.